Free surface effects on stress-driven grain boundary sliding and migration processes in nanocrystalline materials. (December 2016) - Ovid'ko, I.A.; Sheinerman, A.G.
Abstract: The free surface effects on grain boundary (GB) deformation mechanisms mediated by GB sliding and migration processes in nanocrystalline materials are theoretically described. Particular attention is devoted to the specific features of the GB sliding and the cooperative GB sliding and migration processes occurring near free surfaces in nanocrystalline materials. The critical stresses, energies and geometric parameters which characterize the GB deformation mechanisms in question are calculated. The role of the free surface effects in the interpretation of experimental data on the GB sliding and migration processes in nanocrystalline materials is discussed. Graphical abstract: Image 1